Sistem Informasi Koordinat Prakiraan Daerah Penangkapan Ikan Tuna Bagi Nelayan - Sugiari Sugiari (Politeknik Negeri Malang, 2015)
One of the products of Indonesia's fishery is Tuna. To overcome the increasing demand of the world market, the Ministry of Marine Affairs and Fisheries provides routine information on map information on potential zones of fish, especially Tuna. However, for some fishermen it is relatively difficult to access the map because it requires the internet, so it becomes an obstacle in disseminating information on this fish potential zone map. From the above problems, such as the lack of knowledge of fishermen regarding the condition of the location of tuna points, while the current information is relatively difficult to obtain for some fishermen, so it is necessary to develop a